Contextual Contingency and the Logic of Metatheoretical Homogeneity - Kent B. Olson (Current Progress in Arts and Social Studies Research Vol. 7, 2024)
Philosophers talk about theory choice, paradigm shifts, research programs, and so forth. The philosophy of science encompasses three major approaches: the logical approach exemplified by Popper, the sociological approach exemplified by Bloor, and the historical approach exemplified by Laudan. While these approaches are valuable, they may overlook the unique and context-specific aspects of individual scientific changes, leading to Wittgenstein’s fallacy of "seeing what is common". This paper employs case studies as counterexamples to demonstrate how each approach fails to be descriptively exhaustive. The significance of contextual contingencies and individual creativity in scientific innovation has been emphasized. If the line of reasoning is correct, logically, it follows there is no metatheoretical homogeneity. By acknowledging the intricacies of scientific changes, the comprehension of changes within science can be enhanced. The study concluded that the case studies suggest that scientific inquiry is a complex and multifaceted activity. It most definitely cannot be reduced to a single method or approach. Perhaps philosophers need to be more descriptively accurate in our assessments of scientific discoveries. The methodological brushes with which they have hitherto attempted to paint science have been unwieldy, clumsy, and inaccurate. The downside to this more historically accurate view is that the added precision may be less convenient.